Quercetin Alleviates Hyperglycemic-Generated Endoplasmic Reticulum Stress-Contacted Apoptosis of Rat Nucleus Pulposus Cells - Zhen Yu; Xianfeng Wang; Yusen Hu; Xinfa Wang; Zhenghuan Zhu; Xu Xu; Yiming Wang; Ailiang Zhang (Balkan Medical Journal)
Background: Previous research has shown that apoptosis of nucleus pulposus (NP) cells contributes to intervertebral disc degeneration (IDD) progression. Endoplasmic reticulum (ER) stress is a reaction to diverse stimuli in eukaryotes and is tightly contacted with apoptosis. Quercetin, a naturally occurring flavonoid, exerts protective effects against degenerative diseases via ER stress. However, the effect of quercetin on NP cell apoptosis remains unclear. Aims: To investigate the influences of quercetin on apoptosis and ER stress in a high-glucose-generated primary NP cell model. Study Design: In vivo animal experimental study. Methods: To investigate the influence of quercetin in a high-glucose-generated NP cell apoptosis model, control, glucose, and glucose + quercetin groups adopted with Sprague-Dawley rats primary NP cells. In the glucose group, cell apoptosis was generated by 200 mm high glucose. In the glucose + quercetin group, 60 µm quercetin was pretreated with NP cells for 2 h before glucose administration. In this research, we examined the change effect of quercetin on NP cell apoptosis, ER stress, and the protein kinase R-like ER kinase (PERK)-eukaryotic translation initiation element 2α (eIF2α)-activating transcription element 4 (ATF4). Results: High glucose decreased the viability and induced ER stress-related apoptosis in NP cells. Quercetin modulated ER stress through the PERK-eIF2α-ATF4 pathway, thereby alleviating the apoptosis rank in NP cells. Conclusion: Quercetin exerts antiapoptotic effects on NP cells, probably through ER stress, thereby showcasing potential as a therapeutic method for treating IDD.